The impact of the active protection of fundamental rights in the administration’s discretion (Euro-Latin American Journal of Administrative Law, 2018)
The objective of the present work is to demonstrate that contemporary conceptions of the fundamental human rights, demand to de State a complex of positive actions that modify its discretion. The article describes two of the consequences of this conception. One, about the possibility to demand them through a trial, where we conclude that despite the difficulties that implies, it is necessary in cases where exist a violation of a minimum standard of satisfaction of these rights. The second defends the necessity to reform the administration to fulfill it´s obligations.
Keywords: fundamental rights; discretion; standard of minimum satisfaction; undetermined law concepts; administration’s reform